Global Media Coverage of China’s BRI A Survey Study - Jabbar A. Al-Obaidi (Journal of Advanced Research in Social Sciences and Humanities, 2025)
Aim: This article aims to survey random global media coverage of the Belt and Road Initiative (BRI) to discuss the positive and negative news stories of the BRI. Equally, the article is designed to examine how the Chinese media responded to international criticism. Remarkably, the Western/global North media appeared to use risk centered frames more frequently (e.g., debt trap, lack of transparency, geopolitical threat, military alliances), especially in high-profile investigative. Methodology: This article surveys how global media cover BRI, utilizing the Global Database of Events, Language, and Tone (GDELT). It identifies words and phrases that shed a negative light on BRI. Using framing and agenda-setting theories, this article addresses three core questions: (1) What evidence do global media present to support claims that Chinese lending practices are harmful or deceptive? (2) How do developing countries benefit long-term from BRI projects? (3) Does the media present a balanced view of BRI’s pros and cons? (4) How does the Chinese media respond to the global media coverage? These three questions led to a discussion of three distinctive views that were introduced to highlight the BRI’s components, including providing funds, introducing an attractive culture, promoting political ideology, foreign policy (soft diplomacy), and mutual understanding. Findings: Utilizing framing and agenda-setting theories revealed that both theories contributed to international diplomatic stances (e.g., European caution, selective engagement, and coverage), domestic policy debates in host countries (balancing sovereignty versus infrastructure needs), and selective public protest in some of the host countries. Agenda-setting techniques in covering the BRI have influenced news stories locally and internationally. On one side, global media coverage highlights the severity of debt, lack of transparency, and increasing unemployment rate among residents of host countries, the so-called threat of China’s geopolitical influence. On the other side, the Chinese media remains active and consistent in countering the negative stories, aiming to correct the negative perception created by some of the global media coverage in China and around the world. The findings demonstrated the importance of economic cooperation and media portrayal in shaping a country’s image, and, in return, the image of the BRI. Implications/Novel Contribution: International reports and critical news stories highlighted the corruption among recipient countries, the lack of transparency, and the issue of national sovereignty. Some countries, such as India, Italy, and others, reversed their foreign and economic policies and declined to continue BRI’s projects. However, the Chinese efforts to refute what they described as “false accusations” produced a counter-messages campaign to create more friendly media ecosystems, but still too weak to convince skeptical Western media coverage. The article offers recommendations for China, European countries, and the BRI beneficiaries to rebuild trust, transparency, and construct high-quality BRI projects, to improve their bilateral and collective economic cooperation, policymaking, and balanced foreign policies.